USING VIDEO RECORDINGS FOR REFLECTIVE FEEDBACK IN SPEAKING LEARNING: STUDENTS’ PROGRESS AND PARENTS’ INSIGHTS - Winda Wulandari; Wisma Yunita; John R. Baker; Dedi Jasrial (JEE (Journal of English Education), 2026)
Video recording is used as a reflective tool to support students’ speaking development, yet limited research has examined how parents interpret these recordings and how their perceptions relate to students’ actual progress. This study investigated how video recordings serve as reflective feedback that connects parental perceptions with students’ speaking improvement. A mixedmethods design was employed involving 30 elementary-level EFL students and their parents. Students completed monthly video-based speaking tasks, while parents observed the recordings at home and provided reflective feedback. Data were collected through a perception questionnaire, pretest–post-test speaking assessments, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, and Spearman’s rho correlation, while qualitative data were analyzed thematically. Findings indicated that parents held positive perceptions of video recordings as a tool for monitoring progress and supporting learning. Students’ speaking performance improved significantly from pretest to posttest (t = –12.138, p < 0.001), particularly in fluency, pronunciation, vocabulary, accuracy, and confidence. Parents also reported clearer progress observations and increased motivation at home. However, the correlation between parental perceptions and students’ speaking scores was weak and non-significant (ρ = -0.050, p = 0.791), suggesting that improvement was driven more by learning activities, especially repeated video reflection, than by parental attitudes alone. Overall, video recordings effectively enhance speaking performance and provide parents with valuable insight into their children’s development, even though parental perceptions did not directly predict learning outcomes.